Lymphocyte subpopulations in patients with multiple sclerosis. Issue 2 (February 1983) - Compston, A
Abstract : Using monoclonal antibodies, peripheral blood helper/inducer (OKT4) and cytotoxic/suppressor (OKT8) lymphocytes were measured in 14 normal controls, 36 patients with multiple sclerosis at different stages of the disease and 15 patients with isolated optic neuritis. Thirty-four of these individuals were studied on two or more occasions at intervals up to 340 days. Patients with multiple sclerosis in relapse had low levels of OKT8 cells (14.07% +/- 3.79) compared with controls (29.42% +/- 4.69) and this abnormality returned to normal within approximately one month of the onset of new symptoms. Further changes occurred with new relapses. Low OKT8 cells were also found in patients with isolated optic neuritis (18.76 +/- 3.71) or progressive multiple sclerosis (19.91% +/- 7.96); the same pattern of recovery was seen in these two groups as in patients with multiple sclerosis in relapse. In 25% patients studied on two or more occasions after an episode of demyelination abnormalities of lymphocyte subpopulations occurred which were not accompanied by new clinical symptoms or signs. Fluctuations of this kind did not occur in controls. The findings have implications for the pathogenesis and management of patients with multiple sclerosis.